A new piece in the puzzle of the Antarctic Biogeography: What do benthic hydroids tell us about the Scotia Arc affinities? - Soto Àngel, J.; Peña Cantero, A. (Polar Biology, 2017)
The biogeography of the Southern Ocean and its subdivisions has attracted the interest of the scientific community for many years, especially for those border regions with great sub-Antarctic influence. The Scotia Arc, located between the Antarctic Peninsula and the Magellan region, has been considered as a biogeographic bridge and hence widely discussed, but there are still gaps in the knowledge of some zoological groups and its inclusion in truly Antarctic waters still constitutes an unresolved topic. The faunistic affinities between the benthic hydroids from the Scotia Arc and those from nearby regions (i.e., High Antarctica, Patagonian region and Bouvet Island) were evaluated with different similarity index and hierarchical analyses in order to put into evidence the biogeographic connectivity among those regions. The results show that the Scotia Arc archipelagos have greater affinity with continental Antarctica than with the Patagonian region, with an increasing similarity while approaching to High Antarctica, highlighting their importance as a biogeographic bridge and the effectiveness of the Polar Front as a major oceanographic barrier. Evidences from the present study on benthic hydroids supports the placement of the whole Scotia Arc within of the Antarctic region. Present data were compared with those from other benthic invertebrates groups to contribute to a better understanding of the biogeography of the Scotia Arc as a whole. Published